The accidental thesis: playing Go with Deleuze and Guattari - Gordan, Christina Ann (Curtin University, 2003)
This thesis uses a reading of Deleuze and Guattarian philosophies, drawn in the main from their companion texts Anti-Oediuus and A Thousand Plateaus, to explore ways in which popular cultural events and texts construct the way we think. The thesis explores how popular narrative produces the conditions of thinking in terms of a state model of subject-identity, and the manner in which this thinking constructs desire in terms of a desire for its own repression. Of particular concern is the danger this thinking has in constructing a populace conductive to the formation of social conditions marked by fascistic political practices. In considering this kind of thinking and its modes of construction, Deleuze and Guattari make a significant shift away from dominant theoretical analysis of power to argue that desire and the capture of desire are the primary agents of state control.The thesis draws on a number of popular cultural mediums and events, working towards a particular exemplary focus on the social conditions in contemporary Australian society. Integrating dialogues with several other key theorists across a broad spectrum of cultural studies concerns, it concludes that the state model reproduces itself throughout history and within different historical and cultural formations as a repetition of minority desires controlling the majority populous through refrains that appropriate plurality and difference. Further, while collective social revolutionary movements have ultimately failed in the past to overcome this repetition, the thesis suggests that Deleuze and Guattaris concepts of becoming through a molecular revolution, aimed at re-constructing the way we think, remains as a positive hope for liberation.